EVALUASI MANAJEMEN PENDIDIKAN KARAKTER SISWA SMAN 2 BANGUNTAPAN - Ngadiya Ngadiya (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
The aim of this study was identify the management of student’s character education SMAN 2 Banguntapan. This study applied a qualitative approach. The data collecting techniques were observation, interview, and documentation. Data collected from that technique were analyzed by using data reduction, data presentation, and verification. The results of this study reveal that the implementation of character education in SMAN 2 Banguntapan has been integrated in school activity on three main form: (1) combine with learning activities, (2) combine with extracurricular activities, (3) combine with cultivation and making people accustomed. The management of student’s character education in SMAN 2 Banguntapan students is consist of: (1) the planning of character education; (2) the organization of character education; (3) the implementation of character education; and (4) the supervision of character education.